Pengaruh Kompensasi Terhadap Kinerja Karyawan Pada PT. JAEIL INDONESIA - Agung Surya Dwianto; Pupung Purnamasari; Tukini Tukini (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2019)
Abstract Compensation is a complicated and classic problem that has plagued the industrial world. As is known that the provision of appropriate compensation which given by the company, is one of the main factors that influence the improvement of employee performance. In Indonesia, the issue of providing compensation has been regulated in the labor law. The government in this case the Ministry of Manpower always emphasizes to all companies operating in Indonesia, in order to obey and implement all provisions regulated by law. This research was conducted at a company located in Bekasi, precisely in Jababeka - Cikarang, which is at PT. Jaeil Indonesia. The purpose of this study is to determine the extent to which compensation can increase employee performance, especially in the Production Department of PT. Jaeil Indonesia. This type of research is quantitative research, in which the objects in this study amounted to 40 employees of the Production Department of PT. Jaeil Indonesia. The analytical method used is a simple linear regression method. Meanwhile, data was collected through questionnaires and analyzed using SPSS version 24. The results of this study indicate that the value of R² is 0.486, meaning the percentage of the effect of compensation for employee performance is 48.6% while the rest is influenced by other variables not examined in this study. The results of the t test show that the value of t count is greater than the value of t table (5.146> 2.048). This shows that the hypothesis used in this study is accepted, that is there is an effect of giving compensation to the performance of employees in the Production Department of PT. Jaeil Indonesia, so companies need to pay attention to employees by adjusting the compensation with the workload they bear according to the prevailing laws and regulations. Keywords: Compensation and employee performance